Effects of a safe transition programme for discharged patients with high unmet needs. Issue 11 (12th March 2019) - Oh, Eui Geum; Kim, Jeong Hyun; Lee, Hyun Joo
Abstract: Aims and objectives: To examine the effects of the Patient‐Oriented Safe Transition programme on 30‐day unplanned readmissions and emergency department visits, medical costs, caregiver burden and patient health‐related quality of life. Background: With the success of hospitals' quality improvement efforts, the number of discharged patients has been increasing. Successful management of discharged patients is needed in order to reduce unplanned readmissions and to improve patient health outcomes. Design: A nonequivalent control group pretest–posttest design. Methods: This study was conducted by following TREND guideline. Eighty‐three patients were assigned to either the intervention ( n  = 40) or control ( n  = 43) group. The intervention group received individual discharge planning by case managers and home visits by homecare nurses followed by telephone calls throughout the month following discharge. The outcome variables measured were 30‐day unplanned readmissions and emergency department visits, medical costs, caregiver burden and patient health‐related quality of life. Data were analysed by paired t test, multivariate analysis of variance and repeated‐measure analysis of variance. Results: The baseline characteristics of the two groups were homogeneous with respect to gender, age, length of hospital stay and medical conditions. In the intervention group, the caregiver burden decreased 30 days after discharge, whereas the control group increased ( F  = 12.888, p  = 0.001). The patient physical ( p  = 0.005) and mental ( p  < 0.001) quality of life of the intervention group were improved more than the control group. Conclusions: This study suggests that nurses can play a significant role during discharge transitions in improving patient outcomes. The Patient‐Oriented Safe Transition programme could be a beneficial service for discharged patients expected to experience high unmet needs. Relevance to clinical practice: The findings of this study provide the evidences on the needs of transition programmes for discharged patients with high unmet needs.